Intra- and Interpopulation Diversity of the Phytopathogenic Fungi of the Microdochium nivale Species - Olga A. Gogoleva; Egor A. Ryazanov; Guzalia Sh. Murzagulova; Sergey N. Ponomarev; Inna B. Chastukhina; Ildar T. Sakhabutdinov; Elena V. Osipova; Gulnaz S. Mannapova; Viktor N. Korzun; Mira L. Ponomareva; Vladimir Yu. Gorshkov (Journal of Fungi)
Our study investigates the intra- and interpopulation diversity of phytopathogenic fungi, using Microdochium nivale as a model organism. A total of 136 strains, representing two populations, were collected from different winter cereal crops (rye, wheat, and triticale) across two agrocenoses. In these strains, we analyzed and compared genetic and phenotypic traits, exploring potential relationships between them. Significant genetic and phenotypic diversity was revealed among the assayed strains, with most exhibiting distinctive genetic features compared to previously characterized strains from other countries. Both populations included highly virulent and lowly virulent strains, with the majority displaying similar virulence levels across different cereal crops. Some strains demonstrated differential virulence toward different crops, and some even exhibited a plant-beneficial effect on rye while being virulent to wheat and triticale. The percentages of strains with specific genetic traits were different in the two analyzed populations. Our study lays the groundwork for identifying genetic markers associated with phenotypic traits in the studied strains, which will aid in developing reliable diagnostics for predicting crop loss risk and improving disease management. Furthermore, it will assist in identifying reliable sources of resistance to M. nivale-induced diseases within the winter cereal gene pool.